2010
DOI: 10.3402/ijch.v69i3.17627
|View full text |Cite
|
Sign up to set email alerts
|

Drowning in Alaska: progress and persistent problems

Abstract: Objectives. The purpose of this study is to evaluate and describe the current problem of drowning in Alaska, measure changes in the rates since earlier studies have been done and compare occupational and non-occupational drowning characteristics. Study design. This is a descriptive observational study, using existing records obtained from several sources to describe and compare drowning victims and event characteristics. Methods. Drowning fatality data were collected from death certificates, law-enforcement re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…A single study [48] reported a decrease in alcohol-related drowning deaths, with an 81% decrease in the 21-year period until 1995 in King County, Washington State. Another study [56] found 53% of drownings deaths in Alaska that occurred while the victim was alone were alcohol-related, compared to 26% of cases where there were witnesses. Another study [56] found 53% of drownings deaths in Alaska that occurred while the victim was alone were alcohol-related, compared to 26% of cases where there were witnesses.…”
Section: Resultsmentioning
confidence: 98%
“…A single study [48] reported a decrease in alcohol-related drowning deaths, with an 81% decrease in the 21-year period until 1995 in King County, Washington State. Another study [56] found 53% of drownings deaths in Alaska that occurred while the victim was alone were alcohol-related, compared to 26% of cases where there were witnesses. Another study [56] found 53% of drownings deaths in Alaska that occurred while the victim was alone were alcohol-related, compared to 26% of cases where there were witnesses.…”
Section: Resultsmentioning
confidence: 98%
“…8 FTI events are an enduring hazard in the Arctic, and residents practicing subsistence lifestyles face relatively high exposure to water hazards throughout the year, including during the winter. 9,10 In addition to the potential for injury and death, the risk of FTI events can cause equipment loss, decrease harvest success and adversely affect mental health. 11,12 Recent anecdotal reports suggest that travel conditions in Alaska are becoming increasingly hazardous, with more FTI events.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, dependence on fish and marine mammals as primary food sources and reliance on commercial fishing for income requires substantial exposure to natural waters, which increases risk for boating and non-boating UI and drowning. In an earlier study, AN people state-wide had drowning fatality rates nearly 4 times that of non-Native Alaskans [22]. The combined boating/non-boating UI mortality from the current analysis shows the disparity has not changed over time; the 12.8/100,000 AN drowning death rate remains 4.2 times that of AKW.…”
Section: Discussionmentioning
confidence: 68%